Analisis Transformasi Digital dalam Manajemen Operasional All You Can Eat pada Hotel X di Solo - M. A. Jaya Damanik; Bekti Nugrahadi; Aditiya Pratama Daryana; Deddy Ray Girsang; Poniman Poniman (Jurnal Intelek Dan Cendikiawan Nusantara, 2026)
Hotel X is a three-star hotel located in the city center of Solo that offers an all-you-can-eat buffet service as its main dining attraction. This study aims to analyze the implementation of digital transformation in the operational management of the all-you-can-eat service at Hotel X Solo using a qualitative case study approach. Data were collected through in-depth interviews with the general manager, food and beverage manager, head chef, and operational staff, participant observation for 14 days, and document analysis. The results show that Hotel X has implemented digital technologies including an integrated property management system, digital inventory management, an online feedback system, and a customer database. This implementation resulted in a 32% reduction in food waste, a 45% increase in inventory turnover, a 25% reduction in food preparation time, and an 18% increase in customer satisfaction. The main challenges faced include staff adaptation to new technology, internet connectivity issues, and budget constraints.